The influence of organization culture on teacher performance of elementary school - Ayu Tahnia; Happy Fitria; Achmad Wahidy (JPGI (Jurnal Penelitian Guru Indonesia), 2021)
This study aims to discover the significant influence of Organization Culture on teacher performance in cluster 1 Rambutan Subdistrict, Banyuasin Regency. This research uses quantitative methods. Data collection techniques using questionnaires and documentation. The data was analyzed using multiple linear regression formulas.The results of this study show that there is a significant influence of Organization Culture on teacher performance of elementary school with a t count value of 4,182 and t table of 1,998 where t count > t table then Ha2 received. The conclusion of this research is that good organization culture where they would actualized teacher performance.